Genetic support for the current discrete conservation unit of the Central European wolf population. Issue 2 (3rd May 2021) - Szewczyk, Maciej; Nowak, Carsten; Hulva, Pavel; Mergeay, Joachim; Stronen, Astrid V.; Bolfíková, Barbora Černá; Czarnomska, Sylwia D.; Diserens, Tom A.; Fenchuk, Viktar; Figura, Michał; de Groot, Arjen; Haidt, Andżelika; et al.
Abstract : The gray wolf Canis lupus range in central Europe is dynamically expanding, reconnecting previously isolated populations. Thus, a recent paper has proposed to merge the current Baltic and Central European (CE) wolf management units, which are no longer isolated by distance. However, recent genetic findings indicate that these two populations are not genetically homogenous. Here we review the most recent data on wolf genetic structure in central Europe and show that even though the CE and Baltic wolves represent the same phylogeographic lineage, their demographic history has resulted in significant genetic structure between these two populations. While the groups are interconnected by moderate gene flow, it is not high enough to reduce the strong founder signal observed in the CE population, suggesting that population dynamics within the CE wolf range are largely independent from those of its source (Baltic) population. Consequently, a management unit combining the CE and Baltic wolves would not form a demographically coherent entity. Thus, we recommend that conservation management units maintain their separate status.